Feasibility Study and Economic Analysis of a Fuel-Cell-Based CHP System for a Comprehensive Sports Center with an Indoor Swimming Pool - Jie Liu; Sung-Chul Kim; Ki-Yeol Shin (Energies, 2021)
Unlike a general commercial building, heating for a building with an indoor swimming pool is highly energy-intensive due to the high energy demand for swimming water heating. In Korea, the conventional heating method for this kind of building is to use boilers and heat storage tanks that have high fuel costs and greenhouse gas emissions. In this study, a combined heat and power (CHP) system for such a building using the electricity and waste heat from a Phosphoric Acid Fuel Cell (PAFC) system was designed and analyzed in terms of its primary energy saving, CO2 reduction, fuel cell and CHP efficiency, and economic feasibility. The mathematical model of the thermal load evaluation was used with the 3D multi-zone building model in TRNSYS 18 software (Thermal Energy System Specialists, LLC, Madison, MI, USA) to determine the space heating demand and swimming pool heat losses. The energy efficiency of the fuel cell unit was evaluated as a function of the part-load ratio from the operating data. The fundamental components, such as the auxiliary boiler, thermal storage tank, and heat exchanger are also integrated for the simulation of the system’s operation. The result shows that the system has a high potential to improve the utilization efficiency of fuel cell energy production. Referring to the local condition of the energy market in Korea, an economic analysis was also carried out by using a specific FC-CHP capacity at 440 kW. The economic benefit is significant in comparison with a conventional heating system, especially for the full-time operating (FTO) mode. The net profit made by comparison with the conventional energy supply system is about 178,352 to 273,879 USD per year, and the payback period is expected to be 6.9 to 10.7 years under different market conditions.